Стихи из журнала - Некрасов Всеволод Николаевич (Прометей, 1989)
Изд. на средства авт. Экземпляры: КХ (20120502) / Инвентарный номер: 957171 / Цена: 2.00 / Сис.шифр: Р2 / Авт.знак: Н 48 / ГРНТИ: 17 / ББК: 84(2)